Prevalence of Anxiety and Depression among Orthopedic Trauma Inpatients - Muntazir Mehdi, Waleed Ali, Muhammad Fahim Qasim, Adil Saidullah, Rizwan Farooq, Abid Munir (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: Orthopedic trauma patients experience anxiety and depression, both of which are undesirable psychological issues. The present study aimed was to determine the prevalence of anxiety and depression. Material and Methods: This cross-sectional study was conducted on 188 orthopedic trauma patients in Orthopaedics Department of Federal Govt. Polyclinic Hospital (FGPC) Islamabad and Wah Medical College / POF hospital Wah Cantt from October 2020 to September 2022. Prior to study conduction, ethical approval from research and ethical committee was taken. Informed written consent was obtained from each individual. Social characteristics, demographic details, and clinical examination were recorded. Hospital anxiety and depression scale (HADS) was used for the assessment of patient’s anxiety and depression. SPSS version 26 was used for data analysis. Results: Of the total 188 patients, there were 112 (60%) male and 76 (40%) females. The overall mean age was 46.82 ± 12.94 years with an age range (15-75 years). Age-wise distribution of patients was as follows: 56 (29.8%) in 15-30 years, 44 (23.4%) in 31-45 years, 38 (20.2%) in 46-60 year, and 50 (26.6%) in 61-75 years. Out of 188 orthopedic trauma patients, the incidence of road traffic accident (RTA) and ground fall was 96 (51.1%) and 92 (48.9%) respectively. The incidence of anxiety and depression before and after orthopedic surgery was 22 (11.7%) and 32 (17%) and 36 (19.1%) and 46 (24.5%) respectively. Anxiety and depression on HADS was 4.12 and 5.21 before surgery and increased substantially to 4.62 and 5.81 after surgery. The incidence of single, double, and triple fracture was 162 (85.2%), 24 (12.8%), and 2 (1.1%) respectively. Conclusion: The present study found that orthopedic trauma in the elderly often leads to emotional disorders. Anxiety and depression levels were low before surgery and increased after surgery in orthopedic trauma patients. However, age, poverty, and gender are directly related to anxiety and depression. Patients with geriatric disorders should be monitored closely by clinicians. Keywords: Orthopedic trauma, Psychological problems, anxiety, depression